Foundations of peer pressure in team production - Ng, Ying Dan (2019)
Although standard economic theory suggests that team production leads to free-riding problems, more organizations are introducing teams in their work processes. This paper explores the various channels in which peer pressure can arise to mitigate the free-rider effect in team production. As an extension of the economic model by Kandel and Lazear (1992), we create a model of peer pressure that arises in two ways. Firstly, peer pressure arises extrinsically through the direct effect of peer evaluations. On the other hand, it can also arise intrinsically due to the differences in a worker’s effort from the exogenous benchmark effort level. We find that the extent of peer pressure is greater when there is full observability as compared to the case where there is variation in observability of effort. The variance in the noise of effort signals also lowers the value of effort in reducing pressure. An evaluation by binary scoring with ranking outcomes could improve performance with the right incentives in place, and tiered rewards in team incentive schemes could intensify the peer pressure. In the situation where benchmark effort is endogenously determined by other workers, a worker’s effort increases other workers’ efforts through exerting pressure on other workers, leading to higher aggregate output. With the peer pressure models, this study shows how the mechanism of peer pressure in various circumstances may address free-riding problems.